Inability to express emotionally in the sterile woman. - Kedach, Fathia (Journal of Human Sciences, 2021)
This study revealed the level of emotional inability of expression in the sterile woman in terms of the Difficulty Describing  sensations, Difficulty  Identifyning  Feeling the Escternally Oriented Thinking in a sample of five women sterile,through the study of quantitative and qualitative and to reach these aims, ,the researcher applied the test (TAS20) descriptive method, content analysis and descriptive statistics. the results showed the onset of emotional inability, given that the inability to express feelings was first in four of the five subjects in the sample researche in the content analysis. The inability to express the sensations the highest dimension with a total value in all subjects evaluated at 217, then comes the dimension 'inability to delimit sensations, evaluated at 114 where it is clear the difficulty of understanding the terms of the Scale (TAS20). Finally the Escternally Oriented Thinking the outside occupies the third place with the score of 113